Adaptive Management looks like it’s here to stay. Here’s why that matters. - Green, Duncan (From Poverty to Power, 2016)
First installment of reflections on my US trip. This is on the rise of adaptive management approaches in USAID, and some of the questions it raises
Keywords: IMPORTANT

Doing Digital Development Differently: Lessons in adaptive management from technology for governance initiatives in Kenya - Prieto Martin, Pedro; Hernandez, Kevin; Faith, Becky; Ramalingam, Ben (MAVC Research Report, 2017)
Development projects don’t always work as planned. This has long been acknowledged by those in the sector, and has led to several approaches that seek to solve complex development problems through enabling and encouraging greater adaptiveness and learning within projects (e.g. Doing Development Differently and Problem-Driven Iterative Adaptation). Digital development projects experience many of these issues. Using technology for transparency and accountability (Tech4T&A) projects in Kenya as case studies, our research analysed the many different theoretical approaches to learning and adaptation, and then tested how these play out in reality. Firstly, we conducted an extensive review of the literature on the spectrum of approaches to adaptive learning. The findings were used to develop a framework through which to analyse adaptiveness at the different layers of complexity in projects (e.g. software design and development, programme design and management). The second part of the research consisted of interviews and focus group discussions with participants in Tech4T&A projects in Kenya. Respondents helped us identify the main characteristics of adaptiveness in their projects (e.g. who needs to adapt, and how and when) and the challenges and issues that inhibit projects’ abilities to be adaptive. This process also revealed how accountability interplays with adaptiveness, and considered how better collaboration flows can enable adaptiveness. From our literature review and empirical study, we draw several conclusions for increasing adaptiveness in digital development projects. These include simplifying the many adaptive theories that abound, increasing responsiveness to project beneficiaries and stakeholders, and for stakeholders to keep on experimenting, networking and advocating.
Keywords: IMPORTANT

Doing Development Differently at Scale - Pellini, Arnaldo; Karetji, Petrarca C.; Soekadis, Ade (Knowledge, Politics and Policymaking in Indonesia, 2018)
In recent decades there has been an increasing recognition that politics and political institutions matter for development. There is also a much greater interest in contextually grounded approaches. This has stemmed from an acknowledgement that purely technocratic approaches to development often result in failure because they do not take into account the nature of political institutions. Nor do they take account of the context in a particular developing country and the interests and incentives of powerful national actors. Policy processes are embedded in specific social, political and organisational contexts. Approaches that focus on implementing universal best practices in evidence-informed policymaking are unlikely to be successful. Instead, what is needed is an approach that takes the local context as the starting point for understanding what issues are relevant to policymakers and developing contextually appropriate solutions. The authors of this chapter reflect on the management approaches and systems that may be required to enable and support large-scale development programmes to be flexible and adaptive to the local policy context and circumstances. The chapter argues that such programmes struggle to adopt adaptive management principle and that to do that at scale requires some changes in the way such programmes are managed.
Keywords: Adaptive Management; Doing development differently; Evidence-informed policymaking; Indonesia; Knowledge sector; Thinking and working politically

Where have we got to on adaptive learning, thinking and working politically, doing development differently etc? Getting beyond the People’s Front of Judea - Algoso, Dave; Hudson, Alan (From Poverty to Power, 2016)
Dave Algoso and Alan Hudson at Global Integrity compare and contrast 9 different initiatives that are all heading in roughly the right direction in aid reform
Keywords: IMPORTANT

One step back, two steps forward: CARE’s journey towards doing development differently - Aston, Tom (Care Insights, 2017)
The Doing Development Different (DDD) community emerged in August 2014 and advocates that (a) the barriers to development are as much political as tec...

Teams that Do Development Differently - Khan, Jehanzeb; Fisher, Annette (Global Policy Journal, 2017)

NGOs Doing Development Differently - Green, Duncan (From Poverty to Power, 2017)
Report back from a meeting of international NGOs to set up a research and practice network on 'Doing Development Differently' that can complement other actors

Thinking and Working Politically – Are We Seeing the Emergence of a Second Orthodoxy? - Teskey, Graham (Governance Working Paper 1, 2017)
There now is a persuasive volume of evidence that demonstrates that capacity and technical knowledge alone are insufficient to change deeply entrenched political interests and bureaucratic norms. These critiques demonstrate that an understanding of power asymmetries is frequently the critical missing ingredient in project design and implementation. Many eminent thinkers have looked at the difference between success and failure in development, and all point to the primacy of domestic politics. This point has not been lost on development agencies and some have tried to provoke greater attention to the role that politics plays. However, this recognition is yet to pass into the mainstream of development practice. Despite the slow but sure accretion of this knowledge the international community seems to be wedded to doing development traditionally. The purpose of this paper is to consider the extent to which a ‘second orthodoxy’ is slowly emerging which can stand alongside, and in some cases may supplant, the ‘first orthodoxy’ of the traditional project framework. Care has to be taken in making this argument, as there is certainly no consensus within the development community on its importance, and even among advocates, there are slightly differing interpretations of what this second orthodoxy looks like. Further, it is not absolutely clear that the two orthodoxies can co-exist. The paper does not call for any ‘paradigm shift’ in how development practitioners conceptualise programs and projects, nor does it demand that the project framework be scrapped; the former would be impossible and the latter undesirable. Equally readers will find no claims that Doing Development Differently or ‘Thinking and Working Politically’ will always and everywhere guarantee better development outcomes. Rather, the paper seeks to summarise how the two orthodoxies differ, where the second orthodoxy now stands, and propose how it can be taken forward in practical terms.

Putting theory into practice: how DFID is doing development differently - Wild, Leni; Booth, David; Valters, Craig (ODI, 2017)
Keywords: IMPORTANT

A Governance Practitioner’s Notebook: Alternative Ideas and Approaches - Whaites, Alan; Gonzalez, Eduardo; Fyson, Sara; Teskey, Graham (OECD, 2015)
The Governance Practitioner’s Notebook takes an unusual approach for the OECD-DAC Network on Governance (GovNet). It brings together a collection of specially written notes aimed at those who work as governance practitioners within development agencies. It does so, however, without attempting to offer definitive guidance – instead aiming to stimulate thinking and debate. To aid this process the book is centred on a fictional Governance Adviser. The Notebook’s format provides space for experts to speak on today’s governance issues: politics, public sector reform and stakeholder engagement. It encourages debate, charts the evolution of donor thinking, and highlights future challenges in the age of the Sustainable Development Goals. Each section introduces both technical issues and major areas of debate, providing ideas for future development support to institutional reform.
Keywords: IMPORTANT

Doing Development Differently at the World Bank: updating the plumbing to fit the architecture - Bain, Katherine A.; Booth, David; Wild, Leni (ODI, 2016)
Keywords: IMPORTANT